Returns to education, cohorts, and the business cycle in Costa Rica: 1987–2008 - Rojas, Luis (2013)
A pseudo-panel approach is used to estimate the returns to schooling (RTS) in Costa Rica. This approach ameliorates the “ability” bias due to the correlation between the level of education and nonobservable characteristics of the individual.We found that RTS are higher for older samples. Once we study the behavior of the RTS -using different settings and estimators- we analyze their correlation withDeaton’s year, cohort and age effects. We found that the income of younger cohorts is greater than the income of older cohorts, once experience and short run fluctuations of the economy are accounted for. This difference in income between generations is explained by differences in levels of education. Other factors that differ between generations seem to be less important to explain their income differences. Finally, we present preliminary evidence suggesting that short run fluctuations of the GDP affect in a greater extent those with less education.